Alteration of gait parameters in a mouse model of surgically induced knee osteoarthritis. (16th April 2018) - Makii, Yuma; Asaka, Meiko; Setogawa, Susumu; Fujiki, Soichiro; Hosaka, Yoko; Yano, Fumiko; Oka, Hiroyuki; Tanaka, Sakae; Fukui, Naoshi; Yanagihara, Dai; Saito, Taku
Purpose: Joint pain is the most common symptom of osteoarthritis (OA); however, its mechanism remains unclarified. The present study investigated hindlimb motion during locomotion on the treadmill using a three-dimensional (3D) motion analysis system with high-speed cameras to evaluate whether this method can be used as an indication of joint pain in a mouse model of surgically induced OA. Methods: We resected the medial meniscus and medial collateral ligament in 8-week old C57BL/6 male mice and performed locomotion recording 6 months post-operatively. Additionally, we performed the same recording after oral administration of the selective cyclooxygenase-2 inhibitor to determine whether alteration of the parameters were associated with joint pain. Results: OA development, characterized by cartilage degeneration and osteophyte formation, was markedly enhanced in the OA group. There was no significant difference between the sham and OA groups in basic gait parameters, including stance duration, swing duration and gait cycle. However, when we divided the gait cycle into four phases and calculated the joint ranges of motion in each phase, the range of motion of the knee joint during the stepping-in phase and the swing duration were significantly decreased in the OA group. These significant differences between the sham and OA groups were diminished by the oral administration of a selective cyclooxygenase-2 inhibitor to the OA group. Conclusion: The present method may be useful to evaluate joint pain in experimental mice and contribute to elucidating the molecular mechanisms of pain in the OA knee joint in combination with genetically modified mice.